THE ROLE OF THE LEGAL DOCUMENTATION AND INFORMATION NETWORK (JDIH) IN INCREASING ACCESS TO INFORMATION - Mulensi, Nanda; Darubekti, Nurhayati; Valentino, Rahmat Alifin (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study evaluates the role of the Legal Documentation and Information Network (JDIH) at the Bengkulu Kemenkumham Regional Office in increasing access to legal information for the public. Access to transparent and easily accessible legal information is essential to increase legal awareness and public participation in the policy process. Using a qualitative descriptive approach, this study examines how JDIH functions as a legal information center and the factors that influence its effectiveness. Data were collected through in-depth interviews with JDIH managers, Regional Office employees, and service users, as well as observations of the legal document management system. The results of the study indicate that JDIH has provided complete, systematic, and online access to legal information. The public can obtain laws and regulations, legal monographs, and free legal consultation services that help them understand applicable laws. In addition, regular updates of legal information also increase the benefits of JDIH for users. However, challenges are still found, such as limited competent human resources, inadequate technological infrastructure, and low accessibility of information for people in remote areas with limited internet access. The level of JDIH utilization is also still relatively low due to the lack of socialization of services to the public. To improve its effectiveness, training is needed for managers, strengthening of technological infrastructure, and wider socialization so that this service is better known. In addition, there needs to be policy support that strengthens the management and distribution of legal information. Collaboration with educational institutions, local governments, and civil society organizations can also expand the reach of information and increase efficiency in the dissemination of legal information. With these steps, JDIH is expected to further contribute to increasing the transparency of legal information and strengthening public participation in legal development in Indonesia.